Deep Sea and Foreign Going : inside shipping, the invisible industry that brings you 90% of everything - George, Rose (London: Granta Publication, 2018)
Revealing the workings and dangers of freight shipping, the author sails from Rotterdam to Suez to Singapore to present an eye-opening glimpse into an overlooked world filled with suspect practices, dubious operators, and pirates --
Keywords: Shipping. -- History; Freight and freightage. -- History